Utilization of modern contraceptives and associated factors among street women in Dire Dawa, Eastern Ethiopia: a mixed study - Alemu Guta; Bezhabh Amsalu; Tadesse Weldamanuel; Alekaw Sema; Legesse Abera; Bekele Simegn Demissie; Yalelet Belay (BMC, 2021)
Plain language summary Street women are a segment of the population in absolute poverty, which they suffer from the major problems of unwanted pregnancy and sexually transmitted diseases. Besides this issue, its consequences necessitate the use of modern contraceptives. This study aimed to determine the utilization and associated factors, and explore the key barriers to modern contraceptive utilization among street women in Dire Dawa. In this study, a community-based cross-sectional study design was conducted among all censuses and 615 reproductive-aged street women from February 16th to April 10, 2021. Face-to-face and in-depth interviews were employed to generate data for both methods. Data were analyzed using the SPSS software version 25 and a thematic approach for quantitative and qualitative, respectively. The findings of this study showed that the proportion of street women who currently used modern contraceptives was 279 (50.3%). Factors significantly associated were age, distance from the health facility, discussion with health professionals, discussion with sexual partners, history of pregnancy, desire time to have a child, and history of rape. The key barriers to using modern contraceptives are fear of side effects, misperceptions, and the desire to have a child. In conclusion: this study demonstrated that the proportion of street women currently using modern contraceptives was low. Health professionals and health extension workers should give health education that integrates well-organized street women's groups and community health extension workers that may help reduce women's fear of potential side effects. To correct the misperceptions and myths about modern contraceptives too.